Analysis of Learning Higher Order Thinking Skill (HOTS) Toward English Subject - Warmadewi, Putu Sri; Agustini, Dewa Ayu Eka; Wedhanti, Nyoman Karina (Universitas Pendidikan Ganesha, 2019)
In line with the 21st century learning of education, 2013 Curriculum (k-13) highlights the development of critical thinking, problem analyzing, problem solving, decision making, and creating something new. It requires teachers to use the new paradigm in designing the lesson plan as well as the assessment, which indicate Higher Order Thinking Skill (HOTS). However, the implementation does not work properly as planned. Therefore this research aimed to analyze the implementation of Higher Order Thinking Skill (HOTS) in terms of designing the content of lesson plans and assessments at SMA Negeri 2 Banjar. This was a qualitative research employing a document study design. The subject of this study was the English teacher in SMA Negeri 2 Banjar. The data were collected qualitatively through observation, documentation and interview. The results showed that Higher Order Thinking Skill (HOTS) was not expressed in the whole of the lesson plan and the assessment, it was covered in several parts of the lesson plan as well as the assessment. The results has the implication for the English teacher to develop the implementation of Higher Order Thinking (HOT) in the content of the lesson plan and assessment holistically.